2017
DOI: 10.1007/s10597-017-0183-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Medicaid Recipients Receiving Persistent Antipsychotic Polypharmacy

Abstract: Antipsychotic polypharmacy (APP) is a common strategy despite guidelines advising against this practice. This article seeks to quantify the prevalence and correlates of APP using Medicaid Analytic eXtract files from 2003 to 2004. Nineteen percent of Medicaid recipients who received an antipsychotic were treated with APP. Individuals who received APP were more likely to be white, male, disabled, between the ages of 18-29, diagnosed with a psychotic disorder, and diagnosed with a higher number of psychiatric con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
4
0
1
Order By: Relevance
“…16 In 2012, their APP rate was 24.6%. 16 Cotes et al 17 found an APP rate of 19% on Medicaid recipients prescribed with AP. In addition, a meta -analysis 12 found a global median of 19.5% of patients on APP.…”
Section: Discussionmentioning
confidence: 99%
“…16 In 2012, their APP rate was 24.6%. 16 Cotes et al 17 found an APP rate of 19% on Medicaid recipients prescribed with AP. In addition, a meta -analysis 12 found a global median of 19.5% of patients on APP.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the rate of antipsychotic polypharmacy (APP) has reached up to 40% (Cotes et al. , 2018 ) despite clinical practice recommendations emphasizing monotherapy (Galletly et al. , 2016 ; Hasan et al.…”
Section: Introductionmentioning
confidence: 99%
“…La polifarmacia es frecuente en la práctica clínica psiquiátrica a nivel mundial (1,2) y también en nuestro medio (3) . Los adultos mayores (≥65 años) son una población vulnerable a la polifarmacia, debido principalmente a los cambios fisiológicos que repercuten en aspectos farmacocinéticos y farmacodinámicos.…”
Section: Introductionunclassified